ZEB1: A Critical Regulator of Cell Plasticity, DNA Damage Response, and Therapy Resistance - Drápela, Stanislav; Bouchal, Jan; Jolly, Mohit Kumar; Culig, Zoran; Souček, Karel (Frontiers in Molecular Biosciences, 2020)
The predominant way how conventional chemotherapy kills fast proliferating cancer cells is the induction of DNA damage. However, chemoresistance remains the main obstacle of therapy effectivity. An increasing number of studies suggest that epithelial-to-mesenchymal transition (EMT) represents a critical process affecting the sensitivity of cancer cells to chemotherapy. Zinc finger E-box binding homeobox 1 (ZEB1) is a prime element of a network of transcription factors controlling EMT and has been identified as an important molecule in the regulation of DNA damage, cancer cell differentiation as well as metastasis. Recent studies have considered upregulation of ZEB1 as a potential modulator of chemoresistance. It has been hypothesized that cancer cells undergoing EMT acquire unique properties that resemble cancer stem cells (CSCs). These stem-like cells manifest enhanced DNA damage response (DDR) and DNA repair capacity, self-renewal or chemoresistance. In contrast, functional experiments showed that ZEB1 induces chemoresistance regardless of whether other EMT-related changes occurred. ZEB1 was also identified as an important regulator of DDR by the formation of a ZEB1/p300/PCAF complex and direct interaction with ATM kinase which was linked to radioresistance. Moreover, ATM can directly phosphorylate ZEB1 and enhance its stability. Downregulation of ZEB1 also reduced the abundance of CHK1; an effector kinase of DDR activated by ATR and induced its ubiquitin-dependent degradation. In this perspective, we focused on the role of ZEB1 in the regulation of DDR and described the mechanisms of ZEB1-dependent chemoresistance.